Role of proteins and soluble peptides as limiting components during the co-composting of agro-industrial wastes. (15th December 2021) - Pérez-Murcia, M.D.; Martínez-Sabater, E.; Domene, M.A.; González-Céspedes, A.; Bustamante, M.A.; Marhuenda-Egea, F.C.; Barber, X.; López-Lluch, D.B.; Moral, R.
Abstract: The agri-food industry is at the centre of the circular economy, since the co-composting of its residual flows allows their management and adds value producing fertilisers. In this work, six composting piles were prepared combining agri-food sludge (AS), different fresh vegetable wastes (pepper waste (P), tomato waste (T), and leek waste (L), and, as bulking agents, vine shoot pruning (VS), garlic stalks (GS) and avocado leaves (AL)). Classical physico-chemical and chemical determinations and advanced instrumental methods (excitation-emission fluorescence (EEM) and gravimetric (TG, DTG and DTA) techniques) were used and compared to assess organic matter evolution and evaluate the quality of the composts obtained. The thermal profiles of the composting processes were viable to show the stabilization of the agri-food sludge with the different materials tested in the mixtures, reaching adequate levels of stabilization of organic matter. Preferential degradation of peptides and proteins was observed by fluorescence. This seemed to induce a limitation in the biodegradation of the remaining organic matter, indicating that these biomolecules are key in composting dynamics, acting as limiting components during the process. The results from thermogravimetric analysis indicated the degradation of labile compounds (e.g., carbohydrates and proteins), the most recalcitrant material becoming predominant at the maturity stage of the composting process. The rise in the thermogravimetric parameter R2 was associated with the increase in the concentration of more refracting compounds, which need more energy for their decomposition. Highlights: Fluorescence and thermal analyses allowed to study biomolecules effect in composting. Proteins and humic/fulvic substances can limit organic matter dynamic in composting. Proteins and peptides constitute a key/limiting component of the composting process.